Partisipasi Masyarakat Dalam Program Keluarga Berencana (KB) Di Kecamatan Bungbulang Kabupaten Garut - Ieke Sartika Iriany; Ade Purnawan; Anggita Yulian Nugraha (Jurnal Pembangunan dan Kebijakan Publik, 2019)
The government issued a Family Planning Program (KB) aims to actualize the population grow balanced and quality family. The essence of national development is human development and the whole Indonesian society. This research is conducted by using descriptive and qualitative approach. Data obtained from participant , places, documentation and archives and regulations that related to research. In this research data source was chosen purposively. The purpose of this research was to describe public participation consisting of interaction and communication that includes the interest, activeness and contibution of society an d to know the factors that encourage the occurrence of barriers internally and externally in the implementation of family planning program in Bungbulang subdistrict Garut The result of this research shows that public participation in the Family Planning program in Bungbulang subdistrict to actualize the population grow balanced and quality family in 2017 has not gone well as expected.this is because the interest, activeness and contibution of society has not been fully provided to the public. The obstacle factors are the societies did not participate in running KB program, lacking of society support and activeness of society. The society does not understand about the task and everything related to the existing program and does not following the development of informaation in DPPKBPPA in Bungbulang subdistrict.